THE EFFECT OF SOCIALIZATION, UNDERSTANDING OF INFORMATION TECHNOLOGY AND ACCOUNTING ON THE APPLICATION OF SMALL AND MEDIUM MICROFINANCE ACCOUNTING STANDARD (SAK-EMKM) TO MSMES AT COFFE SHOP IN TEGALSARI SUBDISTRICT CENTRAL SURABAYA - Moch. Fadil Pratama Putra; Tituk Diah Widajantie (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study is to test the influence of socialization on the application of SAK EMKM on MSMEs Warkop in Tegalsari Subdistrict Central Surabaya, the influence of information technology understanding on the application of SAK EMKM to MSMEs Warkop in Tegalsari District of Central Surabaya, and test the influence of accounting understanding on the application of SAK EMKM to MSMEs Warkop in Tegalsari Subdistrict Central Surabaya. The data used in the study is primary data obtained through questionnaires. The population in this study is food stalls in tegalsari area of Central Surabaya. The data analysis method used is by using SmartPLS 3.0. Sampling is done by purposive sampling technique. The results of this study show that: 1) Socialization Affects the Application of SAK EMKM. 2) Understanding Information Technology Does Not Affect the Application of SAK EMKM. 3) Understanding Accounting Affects the Application of SAK EMKM. Keywords: Socialization, Understanding Information Technology, Accounting Understanding, Application of SAK EMKM, MSMEs